BiPO4 / g-C3N4 composite photocatalyst as well as preparation method and application thereof

The preparation of BiPO4/g-C3N4 composite photocatalyst by hydrothermal solution, the problem of low efficiency of existing photocatalysts is solved, and efficient photocatalytic degradation performance is achieved, especially in degrading tetracycline.

CN119746908APending Publication Date: 2025-04-04QUANZHOU NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411938319.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing photocatalyst efficiency is low, especially the g-C3N4 catalytic materials, which have low separation and transfer efficiency of photogenerated carriers.

Method used

BiPO4/g-C3N4 composite photocatalyst is prepared by hydrothermal at one time to form more heterointerfaces, enhance the contact area between g-C3N4 and BiPO4, and grow BiPO4 in situ on the surface of g-C3N4 through solution thermal reaction to form a stable heterostructure, and enhance structural stability through heat treatment.

Benefits of technology

The photocatalytic activity is improved, and the tetracycline solution with a concentration of 10 ppm can be effectively degraded under visible light excitation, and the preparation method is simple and easy to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746908A_ABST
    Figure CN119746908A_ABST
Patent Text Reader

Abstract

The invention discloses a BiPO4 / g-C3N4 composite photocatalyst and a preparation method and application thereof.The preparation method includes the steps that S1, dicyandiamide is heated to 500-600 DEG C in a muffle furnace at the heating rate of 2-2.5 DEG C / min, the dicyandiamide is heated, the temperature is kept for 3-5 h, and after the temperature in the furnace is cooled to the room temperature, two-dimensional g-C3N4 can be obtained after grinding; s2, adding the g-C3N4 and Bi (NO3) 3.5 H2O prepared in the step S1 into a mixed solution of alcohol, glycol and glycerol, carrying out ultrasonic treatment until the Bi (NO3) 3.5 H2O is completely dissolved, recording as a solution A, putting NaH2PO2 into a polytetrafluoroethylene lining, adding deionized water, recording as a solution B, slowly adding the solution A into the solution B under the stirring action, and continuously stirring for 1-3 hours to form a mixed solution; s3, putting the mixed solution in the step S2 into a drying oven, reacting at 150-200 DEG C for 2-4 hours, centrifuging, washing, drying at 50-70 DEG C, putting into a muffle furnace after drying, heating to 300-400 DEG C at a heating rate of 2-2.5 DEG C / min, keeping the temperature for 2-3 hours, and grinding into powder to obtain the BiPO4 / g-C3N4 composite photocatalyst. The composite photocatalyst can degrade a tetracycline solution, and the preparation method is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalysts, and in particular to a BiPO4 / g-C3N4 composite photocatalyst and a preparation method and application thereof. Background Art

[0002] In both humans and animals, bacterial diseases are cured with antibiotics. However, when antibiotics are used, they are not fully metabolized by the body and are excreted through urine and feces. This means that antibiotics can enter wastewater when flushed down the toilet and enter the environment when discharged into rivers or other bodies of water. Antibiotics in wastewater can have various negative impacts on the environment. For example, antibiotics can contribute to the development of antimicrobial resistance in the environment, posing a serious threat to public health. In addition, antibiotics can accumulate in aquatic organisms, affecting their ability to grow and reproduce.

[0003] Tetracycline, a commonly used antibiotic in human and veterinary medicine, is a contaminant in wastewater and its presence can cause environmental and health problems. Tetracycline can be removed from wastewater through a variety of treatment methods, including physical, chemical, and biological processes. Physical methods include filtration, adsorption, and membrane separation, chemical methods involve photocatalytic degradation, and biological methods can use microorganisms to degrade or metabolize tetracycline. Adsorption is a simple and effective method that can remove a wide range of contaminants, but it may require frequent replacement or regeneration of the adsorbent material. Photocatalytic degradation is a more complex process that requires a catalyst and a light source, but it is more effective in removing certain types of contaminants and does not produce any waste, making it an ideal treatment technology.

[0004] Graphitic carbon nitride (g-C3N4) has attracted wide attention in the field of photocatalysis due to its narrow band gap, low toxicity and high stability. However, single-phase g-C3N4 has certain shortcomings, namely, the high recombination rate of photogenerated carriers. In addition, the photon efficiency of pure phase g-C3N4 in the visible light region is low (~3.5%), which seriously limits its widespread promotion and application. BiPO4 has good photocatalytic performance, but its wide band gap, poor adsorption performance, large volume, size and other problems make BiPO4 less active under visible light irradiation. However, one of the strategies used by researchers to improve the activity of BiPO4 driven by visible light is to combine BiPO4 with other semiconductors to obtain an effective heterostructure, which can enhance surface interactions, charge transfer and visible light response, etc. It is necessary to explore a simpler, more efficient and controllable synthesis method to prepare BiPO4 / g-C3N4 heterostructures with excellent performance. Summary of the invention

[0005] The purpose of the present invention is to provide a BiPO4 / g-C3N4 composite photocatalyst and its preparation method and application, so as to solve the problems raised in the above background technology.

[0006] One of the technical solutions adopted by the present invention to solve the technical problem is:

[0007] Provided is a method for preparing a BiPO4 / g-C3N4 composite photocatalyst, comprising the following steps:

[0008] S1. Heat dicyandiamide to 500-600°C in a muffle furnace at a heating rate of 2-2.5°C / min, and maintain the temperature for 3-5h. After the temperature in the furnace is cooled to room temperature, two-dimensional g-C3N4 can be obtained after grinding.

[0009] S2: Add g-C3N4 and Bi(NO3)3·5H2O prepared in step S1 to a mixed solution of alcohol, glycol and glycerol, and perform ultrasonic treatment until Bi(NO3)3·5H2O is completely dissolved, which is recorded as solution A. Place NaH2PO2 in a polytetrafluoroethylene liner, add deionized water, which is recorded as solution B. Under stirring, slowly add solution A to solution B, and continue stirring for 1 to 3 hours to form a mixed solution.

[0010] S3: placing the mixed solution of step S2 in an oven, reacting at 150-200°C for 2-4h, centrifuging, washing, drying at 50-70°C, placing in a muffle furnace after drying, heating to 300-400°C at a heating rate of 2-2.5°C / min, maintaining the temperature for 2-3h, grinding into powder, and obtaining a BiPO4 / g-C3N4 composite photocatalyst.

[0011] Furthermore, the ratio of g-C3N4:Bi(NO3)3·5H2O:NaH2PO2 is: 0.5g: 0.11-0.33mmol: 0.1-0.5mmol.

[0012] Furthermore, the volume ratio of the alcohol, glycol and glycerol is 10:6:4.

[0013] The second technical solution adopted by the present invention to solve its technical problem is:

[0014] Provided is a BiPO4 / g-C3N4 composite photocatalyst, which is prepared by the above-mentioned preparation method of the BiPO4 / g-C3N4 composite photocatalyst.

[0015] The third technical solution adopted by the present invention to solve its technical problem is:

[0016] Provided is a method for preparing the BiPO4 / g-C3N4 composite photocatalyst as described above, and the application of the BiPO4 / g-C3N4 composite photocatalyst in removing tetracycline.

[0017] Furthermore, the application method includes: adding the prepared BiPO4 / g-C3N4 composite photocatalyst to a solution containing tetracycline, continuously stirring and dark adsorbing for 50 to 70 minutes to make the BiPO4 / g-C3N4 composite photocatalyst adsorption / desorption equilibrium, after the dark adsorption is completed, performing a visible light catalytic reaction under a xenon lamp, reacting for 90 to 240 minutes, filtering and separating to remove tetracycline in the solution.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention aims at the problem of low efficiency of the existing photocatalyst, especially the problem of low separation and transfer efficiency of photogenerated carriers in the g-C3N4 catalytic material, and provides a method for preparing a BiPO4 / g-C3N4 composite photocatalyst by one-time hydrothermal treatment, wherein the prepared A solution and B solution are stirred evenly to form more heterogeneous interfaces, thereby enhancing the contact area between g-C3N4 and BiPO4, thereby enhancing the interface contact, and through the thermal reaction of the solution, BiPO4 is in situ grown on the surface of g-C3N4, and g-C3N4 and BiPO4 further form a close interface contact, forming Stable heterostructure, and then enhance the structural stability of g-C3N4 and BiPO4 through heat treatment, reduce structural deformation during heat treatment, so that the heterostructure formed by heat treatment, the conduction band position of BiPO4 is lower than the conduction band of g-C3N4, and the valence band position is higher than the valence band of g-C3N4. This energy level dislocation helps electrons transfer from g-C3N4 to BiPO4, while holes remain on g-C3N4, improve the electron transfer path between g-C3N4 and BiPO4, effectively separate electrons and holes, reduce their recombination, promote the separation and transfer of photogenerated carriers, and thus improve its photocatalytic activity. The composite photocatalyst can degrade a tetracycline solution of an organic pollutant with a concentration of 10ppm, and exhibits excellent photocatalytic degradation performance under visible light excitation, and its preparation method is simple, easy to operate, and suitable for promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 XRD diagrams of samples prepared in Examples 1 to 7 of the present invention;

[0020] Figure 2 The SEM images of the samples prepared in Examples 1, 2 and 5 of the present invention are shown;

[0021] Figure 3 This is a graph showing the degradation rates of tetracycline using different catalysts prepared in Examples 1 to 7 of the present invention. DETAILED DESCRIPTION

[0022] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1: Preparation of g-C3N4 material

[0024] g-C3N4 was prepared by using a baking valve. First, 10 g of dicyandiamide was weighed and added to a crucible with a lid. The crucible was then placed in a muffle furnace and heated at a heating rate of 2.3 °C / min to 550 °C, where it was maintained for 4 hours. After the temperature in the furnace was cooled to room temperature, the two-dimensional material g-C3N4 was obtained after grinding.

[0025] Example 2: Preparation of one-dimensional BiPO4 photocatalyst

[0026] BiPO4 was prepared by hydrothermal method, and the specific preparation steps were as follows: first, 10 mL of alcohol, 6 mL of glycol, and 4 mL of glycerol were placed in a 100 mL beaker, and then 1 mmol of bismuth nitrate pentahydrate was added, and then ultrasonicated for 20 min until the bismuth nitrate pentahydrate was completely dissolved in the solution, and a clear and transparent solution was obtained, which was marked as solution A; then 1 mmol of sodium hypophosphite was placed in a polytetrafluoroethylene liner, and 10 mL of deionized water was added, and marked as solution B. Solution A was slowly added to solution B while stirring continuously, and after continuous stirring for 2 hours, it was placed in an oven at 180°C for reaction for 3 hours, then centrifuged and washed, and finally dried in an oven at 60°C to obtain a BiPO4 sample.

[0027] Example 3: Preparation of BiPO4 / g-C3N4 composite photocatalyst

[0028] 0.5 g of g-C3N4 prepared in Example 1 and an appropriate amount of bismuth nitrate pentahydrate were added to a 100 mL beaker, and then 10 mL of alcohol, 6 mL of glycol, and 4 mL of glycerol were added to the beaker respectively, and then ultrasonicated for 20 min until the bismuth nitrate pentahydrate was completely dissolved in the solution, which was marked as solution A. The mechanical action of ultrasound can effectively destroy the agglomerates and make the nanoparticles evenly dispersed; then take an appropriate amount of sodium hypophosphite and place it in a polytetrafluoroethylene liner, add 10 mL of deionized water, and mark it as solution B. While constantly stirring, slowly add solution A. Solution B is added and stirred for 1 to 3 hours to form a mixed solution, which can ensure that the two solutions are fully mixed, promote the uniform distribution of nanoparticles, help form more heterogeneous interfaces, increase the contact area between g-C3N4 and BiPO4, and thus enhance the interface contact; the mixed solution is placed in an oven and reacted at 150 to 200°C for 2 to 4 hours to in-situ grow BiPO4 on the surface of g-C3N4, and g-C3N4 and BiPO4 further form a close interface contact to form a stable heterogeneous structure, and then cooled to room temperature. The product was collected by centrifugation or filtration, washed several times with deionized water and ethanol, dried at 50-70°C, placed in a muffle furnace, and heated to 300-400°C at a heating rate of 2-2.5°C / min, and maintained at this temperature for 2-3 hours. High-temperature heat treatment can promote the interface reaction between g-C3N4 and BiPO4, form a more stable heterogeneous structure, enhance the structural stability of g-C3N4 and BiPO4, reduce structural deformation during heat treatment, improve the electron transfer path between g-C3N4 and BiPO4, and enhance Charge transfer efficiency. The heterostructure formed by heat treatment makes the conduction band position of BiPO4 lower than that of g-C3N4, and the valence band position higher than that of g-C3N4. This energy level dislocation helps transfer electrons from g-C3N4 to BiPO4, while holes remain on g-C3N4, improving the electron transfer path between g-C3N4 and BiPO4, effectively separating electrons and holes, reducing their recombination, and promoting the separation and transfer of photogenerated carriers. Grinding into powder, a BiPO4 / g-C3N4 composite photocatalyst is obtained.

[0029] In this example, 0.5 g of g-C3N4 and 0.066 mmol of bismuth nitrate pentahydrate obtained in Example 1 were added to a 100 mL beaker, and 10 mL of alcohol, 6 mL of glycol, and 4 mL of glycerol were added to the beaker, and then ultrasonicated for 20 min until bismuth nitrate pentahydrate was completely dissolved in the solution, which was marked as solution A, and then 0.097 mmol of sodium hypophosphite was placed in a polytetrafluoroethylene liner, added to 10 mL of deionized water, and marked as solution B. Under constant stirring, solution A was slowly added to solution B, and stirring was continued for 2 h to form a mixed solution; the mixed solution was placed in an oven, reacted at 180 ° C for 3 h, cooled to room temperature, and the product was collected by centrifugation or filtration, washed with deionized water and ethanol several times, dried at 60 ° C, placed in a muffle furnace, heated to 350 ° C at a heating rate of 2.3 ° C / min, and maintained at this temperature for 2.5 hours, ground into powder, and a BiPO4 / g-C3N4 composite photocatalyst was obtained, which was recorded as BCN-1.

[0030] Example 4: Preparation of BiPO4 / g-C3N4 composite photocatalyst

[0031] The preparation method of this embodiment is the same as that of Example 3, except that the amount of bismuth nitrate pentahydrate added in the step of Example 3 is changed from 0.066 mmol to 0.110 mmol, and the amount of sodium hypophosphite added is changed from 0.097 mmol to 0.162 mmol. The remaining steps are the same as those of Example 3. The obtained sample of BiPO4 / g-C3N4 composite photocatalyst is recorded as BCN-2.

[0032] Example 5: Preparation of BiPO4 / g-C3N4 composite photocatalyst

[0033] The preparation method of this embodiment is the same as that of Example 3, except that the amount of bismuth nitrate pentahydrate added in the step of Example 3 is changed from 0.066 mmol to 0.154 mmol, and the amount of sodium hypophosphite added is changed from 0.097 mmol to 0.226 mmol. The remaining steps are the same as those of Example 3. The obtained sample of BiPO4 / g-C3N4 composite photocatalyst is recorded as BCN-3.

[0034] Example 6: Preparation of BiPO4 / g-C3N4 composite photocatalyst

[0035] The preparation method of this embodiment is the same as that of Example 3, except that the amount of bismuth nitrate pentahydrate added in the step of Example 3 is changed from 0.066 mmol to 0.221 mmol, and the amount of sodium hypophosphite added is changed from 0.097 mmol to 0.323 mmol. The remaining steps are the same as those of Example 3. The obtained sample of BiPO4 / g-C3N4 composite photocatalyst is recorded as BCN-4.

[0036] Example 7: Preparation of BiPO4 / g-C3N4 composite photocatalyst

[0037] The preparation method of this embodiment is the same as that of Example 3, except that the amount of bismuth nitrate pentahydrate added in the step of Example 3 is changed from 0.066 mmol to 0.331 mmol, and the amount of sodium hypophosphite added is changed from 0.097 mmol to 0.485 mmol. The remaining steps are the same as those of Example 3. The obtained sample of BiPO4 / g-C3N4 composite photocatalyst is recorded as BCN-5.

[0038] In order to understand the composition and structure of each sample, scanning electron microscopy (SEM) and X-ray diffractometer (XRD) were used to characterize the samples.

[0039] Experimental Example 1: Diffraction Pattern Analysis

[0040] The samples prepared in Examples 1 to 7 were subjected to X-ray diffraction by continuous spectrum scanning using an X-ray diffractometer, with a scanning range of 0° to 80° and a scanning rate of 2° / min. The diffraction patterns were analyzed to study the composition of the material and the structural morphology of atoms or molecules inside the material, and to determine whether the preparation was successful.

[0041] X-ray diffraction is widely used to characterize the intercalation structure of polymer / layered nanocomposites. The position of the diffraction peak in the XRD spectrum can reflect the size of the polymer interlayer spacing. Figure 1 The XRD diagrams of the samples prepared in Examples 1 to 7 show that the heterostructured BiPO4 / g-C3N4 composite photocatalyst exhibits characteristic diffraction peaks of BiPO4 and g-C3N4, and a characteristic diffraction peak can be observed at 2θ=27.4°, which is a typical interplanar stacked graphite layered structure belonging to g-C3N4 material. Compared with pure g-C3N4 material, the BiPO4 / g-C3N4 composite photocatalyst also exhibits characteristic diffraction peaks of BiPO4, indicating that the present invention successfully prepares a one-dimensional / two-dimensional BiPO4 / g-C3N4 composite photocatalyst.

[0042] Test Example 2: Scanning electron microscope analysis

[0043] Scanning electron microscopy was used to scan BiPO4, g-C3N4 and BCN-3 samples to observe the microstructure of BiPO4, g-C3N4 and BCN-3 samples.

[0044] Figure 2This is the SEM image of BiPO4, g-C3N4 and BCN-3 samples. We can see that the BiPO4 sample is a one-dimensional nanorod material, and g-C3N4 is a two-dimensional nanomaterial. When the two semiconductors are combined, a one-dimensional / two-dimensional heterogeneous BiPO4 / g-C3N4 composite structure can be observed.

[0045] Test Example 3: Evaluation of photocatalytic degradation performance

[0046] 40 mg of catalyst was added to 80 ml of 10 ppm tetracycline solution, and the mixture was stirred and dark adsorbed for 60 minutes to ensure the adsorption / desorption balance of the catalyst. After the dark adsorption was completed, the xenon light was turned on. After a certain period of time, 4 ml of the reaction solution was centrifuged and the supernatant was tested on a UV-visible spectrophotometer. The experimental results are shown in Figure 3 .

[0047] Figure 3 The tetracycline degradation diagram of different catalysts prepared in Examples 1 to 7. It can be seen from the figure that the BCN-2 sample has the highest photocatalytic activity, and its degradation rate can reach 73.6% after 180 minutes of visible light excitation. Compared with the degradation efficiencies of pure BiPO4 and g-C3N4 samples of 20% and 42.6%, it shows that the prepared BiPO4 / g-C3N4 heterogeneous structure is conducive to the photocatalytic reaction and is an excellent photocatalyst for degrading tetracycline.

[0048] The present invention aims at the problem of low efficiency of existing photocatalysts, especially the problem of low separation and transfer efficiency of photogenerated carriers in g-C3N4 catalytic materials. The present invention provides a method for preparing a BiPO4 / g-C3N4 composite photocatalyst by one-time hydrothermal treatment, wherein the prepared A solution and B solution are stirred evenly to form more heterogeneous interfaces, thereby enhancing the contact area between g-C3N4 and BiPO4, thereby enhancing the interface contact, and in-situ growing BiPO4 on the surface of g-C3N4 through solution thermal reaction, so that g-C3N4 and BiPO4 further form a close interface contact, thereby forming a stable heterogeneous structure. Then, the structural stability of g-C3N4 and BiPO4 is enhanced by heat treatment, and the structural deformation during the heat treatment process is reduced. In this way, the heterogeneous structure formed by heat treatment has a conduction band position of BiPO4 lower than the conduction band of g-C3N4, and a valence band position higher than the valence band of g-C3N4. This energy level dislocation helps electrons transfer from g-C3N4 to BiPO4, while holes remain on g-C3N4, improving the electron transfer path between g-C3N4 and BiPO4, effectively separating electrons and holes, reducing their recombination, and promoting the separation and transfer of photogenerated carriers, thereby improving its photocatalytic activity. The composite photocatalyst can degrade a tetracycline solution of an organic pollutant with a concentration of 10ppm, and exhibits excellent photocatalytic degradation performance under visible light excitation. The preparation method is simple, easy to operate, and suitable for promotion and application.

[0049] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a BiPO4 / g-C3N4 composite photocatalyst, characterized in that: The following steps are involved: S1. Heat dicyandiamide to 500-600°C in a muffle furnace at a heating rate of 2-2.5°C / min, and maintain the temperature for 3-5h. After the temperature in the furnace is cooled to room temperature, two-dimensional g-C3N4 can be obtained after grinding. S2, adding the g-C3N4 and Bi(NO3)3·5H2O prepared in step S1 to a mixed solution of alcohol, glycol and glycerol, and ultrasonicating until Bi(NO3)3·5H2O is completely dissolved, which is recorded as solution A; placing NaH2PO2 in a polytetrafluoroethylene liner, adding deionized water, which is recorded as solution B; while stirring, slowly adding solution A to solution B, and continuously stirring for 1 to 3 hours to form a mixed solution; S3: placing the mixed solution of step S2 in an oven, reacting at 150-200°C for 2-4h, centrifuging, washing, drying at 50-70°C, placing in a muffle furnace after drying, heating to 300-400°C at a heating rate of 2-2.5°C / min, maintaining the temperature for 2-3h, grinding into powder, and obtaining a BiPO4 / g-C3N4 composite photocatalyst.

2. The method for preparing the BiPO4 / g-C3N4 composite photocatalyst according to claim 1, characterized in that: The ratio of g-C3N4, Bi(NO3)3·5H2O and NaH2PO2 is: 0.5g: 0.11~0.33mmol: 0.1~0.5mmol.

3. The method for preparing the BiPO4 / g-C3N4 composite photocatalyst according to claim 1, characterized in that: The volume ratio of the alcohol, glycol and glycerol is 10:6:

4.

4. A BiPO4 / g-C3N4 composite photocatalyst, characterized in that: The photocatalyst is prepared by the preparation method of the BiPO4 / g-C3N4 composite photocatalyst according to any one of claims 1 to 3.

5. A method for preparing the BiPO4 / g-C3N4 composite photocatalyst as described in any one of claims 1 to 3, wherein the BiPO4 / g-C3N4 composite photocatalyst is used for removing tetracycline.

6. The method for preparing the BiPO4 / g-C3N4 composite photocatalyst according to claim 5, characterized in that: The application method comprises: adding the prepared BiPO4 / g-C3N4 composite photocatalyst to a solution containing tetracycline, continuously stirring and dark adsorbing for 50 to 70 minutes to make the BiPO4 / g-C3N4 composite photocatalyst adsorb / desorb in equilibrium, after the dark adsorption is completed, performing a visible light catalytic reaction under a xenon lamp, reacting for 90 to 240 minutes, filtering and separating, and removing tetracycline from the solution.